The Effect of Perceived Quality, Brand Experience and Perceived Risk on the Repurchase Intention of McDonald's Products in Kediri City - Fadhila, Maratus Della; Putri, Kartika Anggraeni Sudiono (Journal of Economics Education and Entrepreneurship, 2024)
This study aims to determine how the influence of perceived quality, brand experience and repurchase intention on repurchase interest in McDonald's products in Kediri City, which is ranked the second most popular fast food restaurant in Indonesia. McDonald's is also one of the pioneers of fast food business in Kediri City where the city is among the richest cities in Indonesia that has successfully recorded the highest Gross Regional Domestic Product (GDP) per capita in Indonesia. This research is a quantitative research with 105 respondents. The sampling technique in this study is non-probability sampling with purposive sampling and data analysis techniques using multiple linear regression. Data analysis was carried out using descriptive statistics with SPSS software version 24. The results showed that perceived quality had a partial significant effect on repurchase intention. Brand experience has a partial significant effect on repurchase intention. Perceived risk has a partial significant effect on repurchase intention. And perceived quality, brand experience and perceived risk have a significant effect simultaneously on repurchase intention.